Day four : a novel - Lotz, Sarah (New York : Little, Brown and Company, 2015)
On the fourth day of a Caribbean cruise, disaster strikes and the ship is stranded in the Gulf of Mexico. Soon supplies run low, a virus plagues the ship, and there are whispered rumors that the cabins on the lower decks are haunted by shadowy figures. When, at last, the ship is spotted drifting off the coast of Key West, the world's press reports it empty. But the gloomy headlines may be covering up an even more disturbing reality.
Originally published: London : Hodder & Stoughton, 2015.
Keywords: Cruise ships -- Fiction; Viruses -- Fiction; Disasters -- Fiction; Suspense fiction